PROHIBITION ON SELLING RICE IN THE TANAH PAJIMATAN KI AGENG SELO GROBOGAN AREA - Wangsanata, Susana Aditiya; Rahayu, Sucik; Triono, Teguh Iman; Khakim, Ahmad Lukman; Jauro, Alfa; Maulidawati, Maulidawati (Al-Qalam, 2024)
The purpose of this research is to uncover the meaning behind the prohibition of selling rice in the area of the tomb of Ki Ageng Selo in Grobogan, Central Java. This research employs a field study method with a qualitative research type. Data analysis uses qualitative descriptive techniques. Data collection techniques are conducted through observation, interviews, and documentation with the caretaker of Ki Ageng Selo's tomb, Mr. Abdul Rohim, and traders in the area of the tomb. The results of this study indicate that the meaning of the prohibition on selling rice in the area of Ki Ageng Selo's tomb is a teaching to become generous individuals, to honor guests, and to possess a high social spirit. The teaching of generosity is demonstrated by Ki Ageng Selo through the provision of food (ingkung), which is a whole chicken cooked for guests. The teaching of honoring guests is shown through Ki Ageng Selo's concern in the way he serves guests with warmth. The teaching of having a high social spirit is reflected in the respect and appreciation for guests who come. This phenomenon serves as a lesson for the community, especially the people of Selo, that it is essential to possess a generous nature, to honor guests, and to have a high social spirit. The findings indicate that the experiences of a scholar with karomah (spiritual power) can become teachings or advice that are adhered to by the community. The advice given by Ki Ageng Selo to his descendants not to sell rice around his house has become a tradition to this day. If this tradition is violated, the community in the area of Ki Ageng Selo's tomb believes that misfortune will befall the traders who sell rice.